Radiation shielding properties of the doped carbon fiber-reinforced epoxy composites - Erdem, Serkan; Bulut, Fatih; Ozcan, Mehmet Erbil; Ogul, Hasan; Yildiz, Yunus Onur (Pergamon-Elsevier Science Ltd, 2023)
In this study, the linear attenuation coefficients of the doped carbon fiber-reinforced epoxy composites (Boron Oxide (B2O3), Lead Monoxide (PbO) and Zinc Borate (2ZnO 3B2O3 3H2O)) for the gamma radiation are inves-tigated with the help of the High Purity Germanium (HPGe) Detector. The doped carbon fiber-reinforced epoxy composites were prepared with different proportions of additive materials (10, 20, and 30 wt%) so that impact of the additive amount on radiation shielding could be properly analysed. The specimens were tested at 7 different energy levels ranging from 82.0 to 1332.0 keV with the use of HPGe detector. Further on, the effect of additive materials on mechanical properties was also examined. Findings indicate that all additives into composite ma-terials improve the gamma attenuation ability, and the best gamma shielding characteristic is obtained in the case of 30 wt% Lead Monoxide sample. On the other hand, 10 wt% additive materials provide increase in stiffness compared with undoped samples.
Keywords: Radiation shielding; Carbon fiber-reinforced epoxy composites; Radiation protection efficiency